Sistem Informasi Persediaan Barang Pt. Herbal Tirta AbadiDengan Teknologi Single-Page Application Berbasis Web - Tama, Wahana Aditya; , Bana Handaga, S.T.,M.T.,P.h.D (2017)
Before the web-based inventory system, PT HERBAL TIRTA ABADI used manual way by collecting all data of drinking water product selling from production outcome until product selling manually. It made owner and employees of PT HERBAL TIRTA ABADI become overwhelmed in data management when exceeding. This study aims to create computerized inventory system with simple display. The stages in solving this research system consist of requirements analysis, design, implementation, and application test. In making web-based inventory system PHP programming language and Xampp software are used. The results of this system are the users are able to manage products easily, performing complete transaction with facture, and process the reports completely. The display using single page application technology can make the website looks mild and simple. According to respondents assessment questionaire which have already shared, it stated average satisfaction at 83% and makes the operational of PT. HERBAL TIRTA ABADI become easier.